2018
DOI: 10.5812/ijhls.83508
|View full text |Cite
|
Sign up to set email alerts
|

Studying Quality of Drinking Water and Determining Sustainable Indicators for Water Resources of Villages of Harsin Town of Iran

Abstract: Background: Scale formation and corrosion continue to cause mild and serious problems in water dispensing systems. Although there are advanced technologies available today, such problems still persist and can lead to health problems and financial damage. Objectives: To delve into this matter, the present study aimed to determine the water potential in terms of scale formation and corrosion in the water resources of villages in the vicinity Harsin town in Iran. Furthermore, the physical and chemical qualities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Having too soft water is problematic too; in addition, soft water on the other hand is corrosive. This lowers the water quality; consequently, the quality requirements at the consumer's end might not be met anymore (Gray 2008;Mohammadi et al 2018;Honarbakhsh 2019). World Health Organization (WHO) suggested that the permissible range of sodium, magnesium, potassium, calcium, sulfate, chloride and nitrate contents in drinking water is about 200 mg/L, 50 mg/L, 12 mg/L, 75 mg/L, 250 mg/L, 300 mg/L and 5 mg/L, respectively (WHO 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Having too soft water is problematic too; in addition, soft water on the other hand is corrosive. This lowers the water quality; consequently, the quality requirements at the consumer's end might not be met anymore (Gray 2008;Mohammadi et al 2018;Honarbakhsh 2019). World Health Organization (WHO) suggested that the permissible range of sodium, magnesium, potassium, calcium, sulfate, chloride and nitrate contents in drinking water is about 200 mg/L, 50 mg/L, 12 mg/L, 75 mg/L, 250 mg/L, 300 mg/L and 5 mg/L, respectively (WHO 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such devices included pH meter HANNA-pH 211, HACH-2100 P turbidity meter, and HACH-Dr 5000 spectrophotometer, which are used mostly to measure some of the physiochemical parameters of the water. These devices could not ensure reliable and timely data collection during the water quality monitoring process since they are not deployed permanently in the water but have to be taken to site when required and in most cases, this may be well after the event [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy and precision of the parameters recorded by the smart sensor nodes are compared to the measurements obtained by the field personnel in the laboratory. The choice of using Libelium sensors in this project was influenced by (1) robust sensor construction (sensor modules are housed in a waterproof case); (2) high accuracy in sensor readings; (3) simple setup process and ease of use; (4) cost of sensors and maintenance warranty policy; (5) low energy consumption; (6) reliability; (7) online and offline support through webinars, product training, discussion forum, and technical inquiries through email; and (8) software compatibility with other systems such as Arduino sensor board. These meet the criteria set for selecting sensor devices for water quality monitoring [10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major pollutants found in aquatic environments is phosphorus. The average amount of phosphorus in water resources is < 1 mg/L; exceeding the amounts permitted in water causes a serious threat to the environment, animals, and aquatic life (8)(9)(10). Phosphorus is a limiting factor in lakes.…”
Section: Introductionmentioning
confidence: 99%